UPAYA MENINGKATKAN KETAHANAN PANGAN MELALUI SEKTOR EKONOMI KREATIF KELOMPOK ANADOPAH DUSUN PALASARI - Damayanti, Inda Asri; Asri, Reina Nur; Karwati, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The problem that the community still feels is a lack of ability to develop their skills, therefore there is a need for assistance efforts so that the community obtains competent skills according to their needs. The aim of this research is to determine efforts to increase food security through the creative economy sector of the Anadopah group in Palasari hamlet. Sukahurip village. The results of the study in the field were carried out through a course project program implemented through an edutourism development program in a training program providing handicrafts by making various types of woven forms carried out by the Anadopah group as an effort to increase the creativity of residents in increasing food security. Conclusion: Through the implementation of creative economic skills training activities in the Anandopah group, it is an effort to increase community food security. Keywords: anadopah, creative economy, food security.